Effect of Company Size, Profitability, and Leverage on Tax Avoidance - Amelia Ubu Mukin; Yunia Oktari (eCo-Fin, 2019)
The aim of this research to obtain empirical evidence about the size of firm profitability and leverage, to tax avoidance food and beverage sub-sector plastic and packaging listed in Indonesia Stock Exchange in 2016-2017. Determination of the sample was done by using purposive sampling with the number of samples of 13 companies over a period of 2 years of consecutive observations so that the total sample of 26. This research data using SPSS version 20 with descriptive statistical test, classical assumption test, multiple linear regression analysis, hypothesis test. The results of the research that has been processed shows that the significant value of leverage that is proxied using DER is 0.275, the significant value of profitability proxyed using ROA is 0.001, and the significant value of firm size proxied using LN is 0,000. The results of research show that leverage does not have a significant effect on tax avoidance, while profitability and firm size have an effect on the aggressiveness of tax.